Growth of Haematococcus pluvialis Flotow in alternative media - Sipauba-Tavares, L. H. [UNESP]; Berchielli-Morais, F. A. [UNESP]; Scardoeli-Truzzi, B. [UNESP] (Int Inst Ecology, 2015)
Current study investigates the effect of two alternative media: NPK (20-5-20) fertilizer and NPK plus macrophyte (M+NPK) compared to the commercial medium (WC) under growth rate and physiological parameters in batch culture mode (2-L), and verifies whether the use of fertilizer (NPK) and macrophyte (Eichhornia crassipes) would be a good tool for Haematococcus pluvialis culture in the laboratory. The highest number of cells of H. pluvialis has been reported in NPK medium (5.4 x 10(5)cells.mL(-1)) on the 28th day, and in the M+NPK and WC media (4.1 x 10(5) cells.mL(-1) and 2.1 x 10(5) cells.mL(-1)) on the 26th day, respectively. Chlorophyll-a contents were significantly higher (p<0.05) in NPK medium (41-102 mu g.L-1) and lower in WC and M+NPK media (14-61 mu g.L-1). The astaxanthin content was less than 0.04 mg.L-1. Production cost of 10-L of H. pluvialis was low in all media, and NPK and M+ NPK media had a cost reduction of 65% and 82%, respectively when compared with commercial medium (WC). The use of a medium based on commercial fertilizer and macrophyte (E. crassipes) produced a new medium formulation that proved to be efficient, at least in batch culture mode, in promoting high density culture of H. pluvialis. NPK and macrophyte (E. crassipes) medium seems to be an adequate alternative to replace the conventional one (WC).
Keywords: microalgae; NPK (20-5-20); Eichhornia crassipes; biochemical composition; economic aspects